Neurologic Complications in Adult Cancer Survivorship - McGranahan, Tresa Michelle; Figuracion, Karl Cristie; Goldberg, Myron; Sheppard, David P. (Seminars in Neurology, 2024)
Over the past decade, the improvement in cancer diagnostics and therapeutics has extended the overall survival of patients diagnosed with cancer including brain cancer. However, despite these unprecedented medical successes, patients continue to experience numerous neurologic complications after treatment that interfere with their independence, functionality, and overall quality of life. These include, among others, cognitive impairment, endocrinopathies, peripheral and cranial neuropathies, and vasculopathy. This article describes the long-term neurologic complications cancer survivors commonly experience to increase awareness of these complications and discuss treatments when available. Further research is necessary to understanding of mechanisms of neurologic injury and advance diagnosis and treatment. Effective patient education, monitoring, and managing neurologic issues after cancer treatment may improve independence, functionality, and quality of life during survivorship.
Keywords: brain tumor; survivorship; radiation complications; neuropathy